2003
DOI: 10.5551/jat.10.85
|View full text |Cite
|
Sign up to set email alerts
|

R/R Genotype of Human Paraoxonase(PON1) is More Protective against Lipoprotein Oxidation and Coronary Artery Disease in Japanese Subjects.

Abstract: Human paraoxonase (PON1) is an high-density lipoprotein (HDL) -associated enzyme that is proposed to protect against the oxidation of lipoproteins. Recently, the association of coronary artery disease (CAD) and PON1 activity was reported. Furthermore, the R/R genotype of PON1 has been related to the risk for CAD. In this study we investigated the PON1 genotype and susceptibility to lipoprotein oxidation to elucidate the contribution of PON1 to atherosclerosis in Japanese subjects. We studied 179 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…To date, multiple studies have examined the association between PON1 polymorphism and CAD 4, 13, [15][16][17][18][19][20][21][22][23][24][25][26] ; however, the vast ma- jority of studies neither concurrently assessed PON1 activity nor its relevance with the extent of angiographically documented atherosclerosis. In this study, we aimed at evaluating the relationship of PON1 (Q192R polymorphism and activity) with both CAD risk and the extent and severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, multiple studies have examined the association between PON1 polymorphism and CAD 4, 13, [15][16][17][18][19][20][21][22][23][24][25][26] ; however, the vast ma- jority of studies neither concurrently assessed PON1 activity nor its relevance with the extent of angiographically documented atherosclerosis. In this study, we aimed at evaluating the relationship of PON1 (Q192R polymorphism and activity) with both CAD risk and the extent and severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…R allozyme is less efficient at preventing the oxidation of LDL than the Q allozyme because of the decreased hydrolysis of lipid peroxides 13,14) . Hypothesized differences in the ability of the polymorphic forms to protect the oxidation of LDL have led to numerous studies attempting to determine the relationship between PON1 polymorphism and cardiovascular disease 4,13,[15][16][17][18][19][20][21][22][23][24][25][26] . These studies have yielded apparently conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of HDLcholesterol in the Japanese population are higher than those reported in Caucasian populations [4,5]. This favorable lipid profile may be one of the explanations for the lower morbidity of CHD in Japanese populations [6]. Also, there is a growing consensus in support of high HDL-cholesterol as an additional therapeutic target to promote longevity [7].…”
Section: Introductionmentioning
confidence: 96%
“…The results obtained in the present study have confirmed previous suppositions 16) . It is known that the presence of anti-oxidative vitamins, such as ubiquinol-10, and anti-oxidative enzymes, paraoxisonase [32][33][34] , platelet-activating factoracetylhydrolase 35,36) and glutathione peroxidase 37) in HDL, suppresses the formation of lipid peroxides.…”
Section: Discussionmentioning
confidence: 99%